Socio-Pedagogical Support of Child’s Personality Socialization at the Stage of Preschool Childhood Social Formation - Rohalska-Yablonska, Inna P.; Melnyk, Nataliia I.; Dovbnia, Sofiia O.; Lisovska, Tetiana A.; Perkhailo, Nelia A. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: This paper is directed at development and experimentally test the effectiveness of the system of socio-pedagogical support of socialization of the individual; determining the pedagogical conditions for ensuring the harmonious socialization of children in preschool education. The basis of the analysis of the project of social and pedagogical support of the child’s socialization is its humanitarian direction. Background: The relevance of the study is the creation and development of a system of socio-pedagogical support of personality socialization in preschool childhood was confirmed. Method: The implementation of certain tasks was carried out using a set of research methods: the theoretical method, which allows a systematic analysis of philosophical, psychological, sociological, cultural, and pedagogical scientific and methodological literature on socialization, education, and personal development; the empirical methods (observation, interviews, surveys, questionnaires, testing, the study of documentation), which allow to comprehensively consider the specifics of pedagogical activities of teachers to implement the socialization process and levels of socialization of children. Results: The results of the experimental test of the system of social and pedagogical support of personality socialization in preschool childhood developed by us proved its effectiveness, which confirms the quantitative and qualitative changes in the levels of socialization of preschool children. Conclusion: The paper established the state of awareness of preschool teachers with the processes of socialization of the child in preschool childhood; criteria, indicators, and levels of personality socialization in preschool childhood; the pedagogical conditions for the effective course of the process of socialization of children in preschool educational institutions.